Acquiring Combat Capability through Innovative Uses of Public-Private Partnerships - Buchanan, Steven M.; Cabell, Jayson W.; McCrary, Daniel C. (2006)
The purpose of this research is to study the federal government's historical use of public-private partnerships (PPPs) and their view on the issue. Then we study recent applications (case studies) of innovative financing arrangements by Hannon Armstrong, LLC, an Annapolis, Maryland based financial services firm. The intention is to build upon previous Naval Postgraduate School research efforts in this subject; specifically, expanding upon the efforts of Professor San Miguel, Shank and Summers by investigating current examples of PPPs. First, we examine Hannon Armstrong's "fee for service contract" solution to the lack of appropriated capital funds needed for a vital fiber-optic link near the Arctic Circle. Then, we will explore the history of the Energy Saving Performance Contracts (ESPCs), which have been a useful tool in reducing the energy consumption throughout the federal government. Historically, this program has only been used for fixed assets. There is little debate over the success of these contracts in reducing energy consumption. The authors believe tat applying Energy Savings Performance Contracts to mobile assets could further reduce the energy consumption of the Department of Defense (DoD) and save tax-payers millions of dollars. The original document contains color images.